2015
DOI: 10.1002/alr.21512
|View full text |Cite|
|
Sign up to set email alerts
|

Intradermal testing after negative skin prick testing for patients with high suspicion of allergy

Abstract: Approximately 20% of all negative results on SPT will have a positive ID test, more likely for indoor allergens. If a high suspicion for allergy exists in a patient with a negative SPT result, it may be useful to proceed with ID testing. However, the clinical significance of a positive ID test after negative SPT still needs to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Other studies demonstrated that, the higher the concentrations used for IDST, the more likely it is to diagnose sensitizations. 2,9,10,12,15 In our retrospective study, we combined the results of patients treated at different hospitals, which used different protocols for IDST. Even though this may be considered a bias or a lack of standardization, different allergen concentrations used for IDST are widely used in the clinical practice: e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies demonstrated that, the higher the concentrations used for IDST, the more likely it is to diagnose sensitizations. 2,9,10,12,15 In our retrospective study, we combined the results of patients treated at different hospitals, which used different protocols for IDST. Even though this may be considered a bias or a lack of standardization, different allergen concentrations used for IDST are widely used in the clinical practice: e.g.…”
Section: Discussionmentioning
confidence: 99%
“…, ImmunoCap [Phadia, Uppsala, Sweden] and Immulite [Siemens Health Care Diagnostics, Tarrytown, NY]) have been shown to be as sensitive as SPT. 17 Hence, the American Academy of Pediatrics 8 and Asthma Management guidelines set forth by the National Asthma Education and Prevention Program 5 in 2007 recommend either SPT or ssIgE testing to establish a diagnosis of environmental allergies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Skin prick test is the first‐line diagnostic tool to confirm allergic sensitization. As prick test results may be negative or elicit skin test reactions to allergens that do not fit the period of the observed subjective complaints, intradermal test might serve as a further diagnostic tool . Intradermal test is also valuable especially in revealing hypersensitivity to penicillin, insect venoms, insulin, heparins, muscle relaxants, chemotherapeutic agents and biologics .…”
Section: Introductionmentioning
confidence: 99%
“…As prick test results may be negative or elicit skin test reactions to allergens that do not fit the period of the observed subjective complaints, intradermal test might serve as a further diagnostic tool. [9][10][11][12] Intradermal test is also valuable especially in revealing hypersensitivity to penicillin, insect venoms, insulin, heparins, muscle relaxants, chemotherapeutic agents and biologics. [13][14][15] Depending on the allergen used, intradermal test is performed using a suitable dose, i.e., 30 lg of major allergen for inhalant allergies and injected at a volume of 0.02-0.05 mL.…”
Section: Introductionmentioning
confidence: 99%